[11C]Raclopride binding in the striatum of minimally restrained and free‐walking awake mice in a positron emission tomography study. Issue 12 (1st October 2015) - Takuwa, Hiroyuki; Maeda, Jun; Ikoma, Yoko; Tokunaga, Masaki; Wakizaka, Hidekatsu; Uchida, Shouko; Kanno, Iwao; Taniguchi, Junko; Ito, Hiroshi; Higuchi, Makoto
ABSTRACT Anesthesia and restraint stress have profound impacts on brain functions, including neural activity and cerebrovascular function, possibly influencing functional and neurochemical positron emission tomography (PET) imaging data. For circumventing this effect, we developed an experimental system enabling PET imaging of free‐walking awake mice with minimal restraints by fixing the head to a holder. The applicability of this system was investigated by performing PET imaging of D2 dopamine receptors with [11C]raclopride under the following three different conditions: (1) free‐walking awake state; (2) 1.5% isoflurane anesthesia; and (3) whole‐body restraint without anesthesia. [11C]raclopride binding potential (BPND) values under isoflurane anesthesia and restrained awake state were significantly lower than under free‐walking awake state (P < 0.01). Heart rates in restrained awake mice were significantly higher than those in free‐walking awake mice (P < 0.01), suggesting that free‐walking awake state minimized restraint stress during the PET scan. [11C] raclopride‐PET with methamphetamine (METH) injection was also performed in awake and anesthetized mice. METH‐induced reduction of [11C]raclopride BPND in anesthetized mice showed a trend to be less than that in free‐walking awake mice, implying that pharmacological modulation of dopaminergic transmissions could be sensitively captured by PET imaging of free‐walking awake mice. We concluded that our system is of utility as an in vivo assaying platform for studies of brain functions and neurotransmission elements in small animals, such as those modeling neuropsychiatric disorders. Synapse 69:600–606, 2015. © 2015 Wiley Periodicals, Inc.